Total knee arthroplasty and femoral osteotomy with a patient-specific cutting guide to treat haemophilic arthritis with severe extra-articular deformity: A case report and review of literatures - Lv, Shuai-Jie; Wang, Zheng-Ming; Wang, Rui; Jin, Heng-Kai; Tong, Pei-Jian; Liu, Xun (Frontiers in Surgery, 2023)
BACKGROUND Total knee arthroplasty (TKA) is recommended for haemophilic patients with end-stage arthritis. TKA combined with a one-stage extraarticular osteotomy is uncommon in the treatment of haemophilic arthritis (HA) with severe extra-articular deformities (EADs) and a history of inhibitors under the guidance of a patient-specific cutting guide (PSI). CASE presentation We reported a 20-year-old male patient with severe haemophilia, limited knee functionality, a 30° sagittal deformity on the femoral side and a history of inhibitors. We adopted the Van Creveld protocol to decrease the inhibitors. TKA and extra-articular osteotomy (EAO) were performed simultaneously and sequentially under the guidance of PSI. An appropriate central alignment of the lower limb was restored by using cement prostheses with antibiotics and femur shaft locking compression plates. The last follow-up showed that the knee function was good, the VAS score was 0, the WOMAC score was 18 and the ROM was 0°-95°. CONCLISION Regular haematology management can reduce the perioperative bleeding risk in haemophilic patients treated with inhibitors. PSI plays an important role in guiding the TKA and EAO of end-stage HA patients with severe EAD.